Giant Angiomyoma of the Broadligament: A Case Report - Güven, Davut; Erdoğan, Özgür; Kılıco, İsmail and Koçak, İdris and Üstün, Cazip (Gynecology Obstetrics & Reproductive Medicine, 2009)
Angiomyoma of broad ligament region is rare and there is only one reported case of angiomyoma of this region in the literature. A 43 year old women was operated because of broad ligament mass. The pathologic examination revealed broad ligament angiomyoma. It was amed to report the present case regarding its extremely rare localisation for angiomyoma.